Computed Tomography Assessment of Retained Testes in Dogs - Stefano Spada; Daniela De Felice; Alfonso Calabria; Francesca Carletti; Luiz Paulo Nogueira Aires; Massimo Vignoli; Martina Rosto; Marco Russo (Animals)
Cryptorchidism consists in the failure of one or both testicles to fully descend into the scrotum. The position of the retained testes can be abdominal or inguinal and may occur unilaterally or bilaterally. This retrospective, multi-center study aimed to describe the computed tomography (CT) features of retained testes in dogs. Nineteen CT scans of dogs, with either unilateral or bilateral cryptorchidism, were analyzed with both pre- and post-contrast imaging. The location, size, shape, margins, homogeneous parenchyma, and density calculated were examined with the Hounsfield unit. Statistical analyses were performed to assess the differences between the scrotal (ST) and undescended testes (UT) and to detect any correlation between the features, ages, and size of the dog. CT identified the retained testes and provided enhanced three-dimensional visualization compared to traditional ultrasound. This study revealed that the UT were significantly smaller than ST, with UT measuring around 70% of ST size. Additionally, the UT exhibited increased density in both pre- and post-contrast scans, potentially due to the reduced or absent spermatogenesis or to histological changes occurring in the parenchyma. While CT showed clear advantages, such as three-dimensional spatial resolution and deeper tissue penetration, limitations such as general anesthesia and radiation exposure should also be considered. However, the present study showed that CT could serve as a valuable second step tool in cases where ultrasound fails, particularly in challenging anatomical situations.